Surveillance of animal diseases [1] - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2001)
Manual on Livestock Disease Surveillance and Information Systems. FAO, 1999. FAO Animal Health Manuals number 8. 78 pp.